(untitled) (International Journal of Engineering and Computer Science, 2015)
Vehicular Network is a recently developed technology which will be very beneficial for reducing the roadside accidents which are caused due to the rapid increase in number of vehicles on the road. VANET is an ad hoc network where vehicles act as the communicating nodes. Communication among the vehicles and with roadside unit helps in maintaining coordination which ensures control of traffic congestion on roads which in turn reduces environmental pollution. For the proper implementation of the Vehicular Network, the most important aspect is efficient routing of packets in the network and hence a careful study is required to choose the best routing protocol. In this paper, a performance analysis of both proactive (DSDV) and reactive (AODV) protocol is carried out for different parameters like throughput, net routing load and end to end delay to compare their performance in different scenarios. Finally the pros and cons associated with each protocol are detected and a new approach is proposed which aims to solve the problems associated with routing